Anticholinergic burden in schizophrenia and ability to benefit from psychosocial treatment programmes: a 3-year prospective cohort study. Issue 15 (31st August 2016) - O'Reilly, K.; O'Connell, P.; Donohoe, G.; Coyle, C.; O'Sullivan, D.; Azvee, Z.; Maddock, C.; Sharma, K.; Sadi, H.; McMahon, M.; Kennedy, H. G.
Abstract : Background: Many medications administered to patients with schizophrenia possess anticholinergic properties. When aggregated, pharmacological treatments may result in a considerable anticholinergic burden. The extent to which anticholinergic burden has a deleterious effect on cognition and impairs ability to participate in and benefit from psychosocial treatments is unknown. Method: Seventy patients were followed for approximately 3 years. The MATRICS consensus cognitive battery (MCCB) was administered at baseline. Anticholinergic burden was measured with the Anticholinergic Cognitive Burden (ACB) scale. Ability to benefit from psychosocial programmes was measured using the DUNDRUM-3 Programme Completion Scale (D-3) at baseline and follow-up. Psychiatric symptoms were measured using the PANSS. Total antipsychotic dose was measured using chlorpromazine equivalents. Functioning was measured using the Social and Occupational Functioning Assessment Scale (SOFAS). Results: Mediation analysis found that the influence of anticholinergic burden on ability to participate and benefit from psychosocial programmes was completely mediated by the MCCB. For every 1-unit increase on the ACB scale, change scores for DUNDRUM-3 decreased by −0.27 points. This relationship appears specific to anticholinergic burden and not total antipsychotic dose. Moreover, mediation appears to be specific to cognition and not psychopathology. Baseline functioning also acted as mediator but only when MCCB was not controlled for. Conclusions: Anticholinergic burden has a significant impact on patients' ability to participate in and benefit from psychosocial treatment programmes. Physicians need to be mindful of the cumulative effect that medications can have on patient cognition, functional capacity and ability to benefit from psychosocial treatments.